2007
DOI: 10.1177/0961203306074842
|View full text |Cite
|
Sign up to set email alerts
|

Impaired endothelial function in systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) patients suffer from excess cardiac deaths due to accelerated atherosclerosis. Endothelial dysfunction is a marker of early atherosclerosis. We tested the hypothesis that SLE patients have impaired endothelial function and assessed the relationship between endothelial function and clinical outcome over the subsequent five years. Thirty-six female SLE patients were compared with 22 healthy age and sex matched controls. Endothelial dependent vasodilatation (EDD) was assessed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 20 publications
2
29
1
Order By: Relevance
“…The effect of atorvastatin on FMD in our study was independent on baseline serum lipids levels, corroborating previous studies in patients with hypertension [31], diabetes mellitus [32] and dyslipidaemia [33], and supporting the notion that the endothelial benefits of atorvastatin are independent of the reduction in serum lipids levels. In the present study we also confirmed previous findings of reduced FMD in SLE patients as compared to healthy controls, suggesting significant endothelial dysfunction in SLE patients [14,34,35].…”
Section: Discussionsupporting
confidence: 81%
“…The effect of atorvastatin on FMD in our study was independent on baseline serum lipids levels, corroborating previous studies in patients with hypertension [31], diabetes mellitus [32] and dyslipidaemia [33], and supporting the notion that the endothelial benefits of atorvastatin are independent of the reduction in serum lipids levels. In the present study we also confirmed previous findings of reduced FMD in SLE patients as compared to healthy controls, suggesting significant endothelial dysfunction in SLE patients [14,34,35].…”
Section: Discussionsupporting
confidence: 81%
“…(Katušic and Vanhoutte 1986;Rubanyi and Vanhoutte 1986 a,b;Rubanyi 1988;Yanagishawa et al 1988;Lüscher et al 1992). It participates and plays a substantial role in the generation of various diseases like atherosclerosis (Ross 1993(Ross , 1999Heitzer et al 1996;Besler et al 2008;Heistad 2008), essential hypertension (Lüscher 1988;Vanhoutte 1992;Taddei et al 1995;Besler et al 2008), diabetes mellitus and diabetic vasculopathies (Makimattila et al 1996;Bakker et al 2009;Nathanson and Nyström 2009), chronic obstructive pulmonary disease -COPD (Peinado et al 2008), rheumatoid arthritis (Hansel et al 2003;Szekanecz and Koch 2008), psoriatic arthritis (Gonzalez-Juanatey et al 2007), osteoarthritis (Miller et al 2007), ankylosing spondylitis (Sari et al 2006), systemic lupus erythematosus (Piper et al 2007), cancer metastasis (Johansson et al 2010;Takala et al 2010), migraine and stroke (Besler et al 2008;Elliott 2008), anaphylactic and traumatic shock (Menardi et al 2006;Shi et al 2007;Nakashidze 2009), systemic inflammatory response syndrome (Neary and Redmond 1999;Hingorani et al 2000;Menardi et al 2006), NO-induced vasoplegia in sepsis (Stawicki et al 2008;Funk et al 2009) and cardiac surgery …”
Section: The Endotheliummentioning
confidence: 99%
“…Due to microangiopathy, ophthalmologic, neurologic and nephrologic complications may occur. Microangiopathies are characterized by roughed-up basal membrane, proliferation, focal desquamation and alteration in endothelium cell shape, stack of granulocytes and adherence of platelets to the endothelium (Pieper and Gross 1991). The wall of small blood vessels becomes so thick and weak that they bleed, leak protein, and reduce blood flow.…”
Section: Progression Of Diabetes Mellitus and Endothelial Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial dysfunction has been demonstrated in SLE using brachial artery Doppler ultrasound (7). However, such measurements are unable to detect subclinical atherosclerosis.…”
mentioning
confidence: 99%